2021
DOI: 10.1111/hex.13139
|View full text |Cite
|
Sign up to set email alerts
|

Living beyond the limitation: Rehabilitation, life and productivity of individuals with schizophrenia in South‐West Nigeria

Abstract: Introduction Schizophrenia, the most chronic and stigmatized form of mental illness, can be described as a brain disorder that affects an individual's cognition. Individuals with schizophrenia exhibit socially unacceptable symptoms that affect their psychosocial lives. They suffer from reduced productivity due to the debilitating effect of the illness, and the negative symptoms impede their employability; such symptoms and effects aggravate the stigma around mental illness. However, when rehabilitation is succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Determining the perception of patients under rehabilitation is imperative to understanding the effect of this therapy. Some previous qualitative studies have evaluated the perceptions of patients and their caregivers and found that motivation needs for people under rehabilitation are different [ 26 28 ]. However, only a handful of these studies have described the long-term effects of rehabilitation in patients, which is common in China, possibly due to different national conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Determining the perception of patients under rehabilitation is imperative to understanding the effect of this therapy. Some previous qualitative studies have evaluated the perceptions of patients and their caregivers and found that motivation needs for people under rehabilitation are different [ 26 28 ]. However, only a handful of these studies have described the long-term effects of rehabilitation in patients, which is common in China, possibly due to different national conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The labelling, together with the burden of caring for an individual with mental illness, causes emotional distress for the family members and increases their chances of developing psychological or related illnesses (Gharavi et al., 2018). People in high‐income countries with schizophrenia and other mental illnesses receive government support through health aids (Yu et al., 2017) or disability pay, as in the United States, through which people are given a stipulated amount as upkeep due to the illness (Whittle et al., 2017); this is not true for those in low‐ to middle‐income countries such as South West Nigeria (Oyelade & Nkosi‐Mafutha, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The feelings of reduced family burden depend on the extent of recovery, which may be evident by the family's expression of relief after rehabilitation (Chen et al., 2019; Fulton et al., 2020). Oyelade and Nkosi‐Mafutha (2021) reported that although rehabilitation services were available in Nigeria, the concept of rehabilitation is misunderstood. This, therefore, makes it important to enquire into what the family expects and experiences with regard to the rehabilitation of their relatives with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%